Una stele ad occhi sudarabica e i primordi della ricerca archeologica italiana nello Yemen: dossier - Jung, Michael (Oriente moderno, 2024)
The squeeze paper of a small South Arabian monument, belonging to the type known as an Eye stele, made in Ṣanʿāʾ in March 1927, and donated in 2020 to the Museum of Oriental Art/Museum of Civilizations, documents a find whose original has gone probably lost, and also witnesses an important moment in the history of Italian relations with Yemen, conducted also through archaeological research.